Isolasi dan identifikasi asam Linolenat dari biji selasih (Ocimum Basilicum) dengan menggunakan metode Soxhlet - Isnaini, Nufia Rohmatul (Maliki Interdisciplinary Journal, 2024)
The basil plant (Ocimum basilicum) is one type of Indonesian endemic plant that has many benefits in every part of it such as leaves, stems and basil seeds. Basil seeds have been used as traditional medicine such as dyspepsia treatment, diarrhea, and anti-inflammatory. Basil seeds are also rich in various nutrients including fiber, protein, omega-3 fatty acids, antioxidants and minerals. Basil seeds can be extracted to produce basil seed oil which is rich in omega-3 fatty acids including linolenic acid, oleic acid, palmitic acid and stearic acid. This practicum was conducted to determine the isolation, physical properties, and characterization of linolenic acid from basil seeds (Ocimum basilicum). The methods used were soxhlet extraction method with n-hexane solvent and oil hydrolysis with base catalyst, KOH. The results obtained from the isolation of α-linolenic acid from basil seeds (Ocimum basilicum) carried out by soxhlet extraction using n-hexane and methanol solvents are the weight of the extracted oil 10.0498 grams with a yield of 20.0996%. Then hydrolysis with KOH and partitioned using n-hexane solvent obtained a yield of 797.7054%. Then physical properties testing was carried out in the form of density and refractive index tests which were obtained 0.969 and 1.357, respectively. after that identification was carried out using GC-MS spectrophotometers.